Mapping the Risk of Fracture of the Tibia From Penetrating Fragments - Nguyen, Thuy-Tien N.; Carpanen, Diagarajen; Rankin, Iain A.; Ramasamy, Arul; Breeze, Johno; Proud, William G.; Clasper, Jonathan C.; Masouros, Spyros D. (Frontiers in Bioengineering and Biotechnology, 2020)
Penetrating injuries are commonly inflicted in attacks with explosive devices. The extremities, and especially the leg, are the most commonly affected body areas, presenting high risk of infection, slow recovery, and threat of amputation. The aim of this study was to quantify the risk of fracture to the anteromedial, posterior, and lateral aspects of the tibia from a metal fragment-simulating projectile (FSP). A gas gun system and a 0.78-g cylindrical FSP were employed to perform tests on an ovine tibia model. The results from the animal study were subsequently scaled to obtain fracture-risk curves for the human tibia using the cortical thickness ratio. The thickness of the surrounding soft tissue was also taken into account when assessing fracture risk. The lateral cortex of the tibia was found to be most susceptible to fracture, whose impact velocity at 50% risk of EF1+, EF2+, EF3+, and EF4+ fracture types – according to the modified Winquist-Hansen classification – were 174, 190, 212, and 282 m/s respectively. The findings of this study will be used to increase the fidelity of predictive models of projectile penetration.